1D Organic Micro/Nanostructures for Photonics. (9th November 2020) - Shi, Ying‐Li; Wang, Xue‐Dong
Abstract: 1D organic micro/nanostructures (OMNSs) based on π‐conjugated molecules are considered to be suitable candidates as photonic units due to their unique photophysical advantages over traditional ones in low‐temperature solution‐processed approach, tunable emission color, the built‐in cavity for optical confinement, and so forth. These inherent characteristics of OMNSs make them have broad application prospects in photonics devices, such as nanolasers, optical waveguides, and optical logical gates. In this review, the recent processes of OMNSs in terms of light generation, light confinement, and propagation are introduced, separately. Some representative works of OMNSs are discussed in the direction of optical modulation and processing. However, huge challenges still remain before the OMNSs are actually used as components of optical circuits in the photonics chips. The summary and the expectations are presented for the future development of 1D organic micro/nanostructures photonics. Abstract : 1D organic micro/nanostructures have great potential in nanoscale integrated optical circuits as photonic components due to their intrinsic capabilities to generate and confine optical signals efficiently. Herein, the recent advances of 1D micro/nanostructures in photonic applications are reviewed. Then, the prospects and suggestions for future development are presented.